Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 2 - Review Exercises - Page 233: 26



Work Step by Step

$f(x)=x^3-5x^2+x$ $\frac{f(x+h)-f(x)}{h}=\frac{((x+h)^3-5(x+h)^2+(x+h))-(x^3-5x^2+x)}{h}$ $=\frac{(x^3+3x^2h+3xh^2+h^3-5(x^2+h^2+2xh)+x+h)-(x^3-5x^2+x)}{h}$ $=\frac{3x^2h+3h^2x+h^3-10hx-5h^2+h}{h}$ $=3x^2+3hx+h^2-10x-5h+1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.